An analysis of the case Kellogg India Private Limited vs. India - Staloch, Maria Eduarda (Revista de Direito Tributário Internacional Atual, 2025)
The present article analyzes the Mumbai Income Tax Appellate Tribunal’s judgment in case No. ITA No. 7342/Mum/2018, involving Kellogg India and the State. Initially, it provides a brief definition of transfer pricing and outlines the tests applicable to intra-group transactions. Subsequently, it examines the methods applied by Kellogg India and the method determined by the Tax Authority, as well as the decision made by the Mumbai Income Tax Appellate Tribunal. Lastly, it will analyze whether the case’s resolution is in line with the OECD Transfer Pricing Guidelines. This study seeks to conclude how to proceed in cases where there is the possibility of applying more than one transfer pricing method.